Prevalence of depression and its impact on quality of life among frontline nurses in emergency departments during the COVID-19 outbreak - An, Ying; Yang, Yuan; Wang, Aiping; Li, Yue; Zhang, Qinge; Cheung, Teris; Ungvari, Gabor S.; Qin, Ming-Zhao; An, Feng-Rong; Xiang, Yu-Tao (Journal of affective disorders, 2020)
•ED nurses exposed to COVID-19 could be psychologically and mentally exhausted.•Prevalence of depression among 1,103 ED nurses was 43.61% (95% CI=40.68%–46.54%).•A heightened awareness of and timely treatment for depression for frontline ED nurses should be provided. Frontline medical staff exposed to the novel coronavirus disease (COVID-19) could be psychologically and mentally exhausted. This study examined the prevalence of depressive symptoms (depression hereafter) and their correlates and the association between depression and quality of life (QOL) in Emergency Department (ED) nurses during the COVID-19 pandemic in China. This national, cross-sectional online survey was conducted between March 15 and March 20, 2020 in China. Depression and QOL were measured using the 9-item Patient Health Questionnaire, and the World Health Organization Quality of Life Questionnaire-Brief Version, respectively. The overall prevalence of depression in 1103 ED nurses was 43.61% (95% CI=40.68–46.54%). Multiple logistic regression analysis revealed that working in tertiary hospitals (OR=1.647, P=0.009), direct patient care of COVID-19 patients (OR=1.421, P=0.018), and current smokers (OR=3.843, P<0.001) were significantly associated with depression. After controlling for covariates, nurses with depression had an overall lower QOL compared to those without (F(1,1103)=423.83, P<0.001). Depression was common among ED nurses during the COVID-19 pandemic. Considering the negative impact of depression on quality of patient care and nurses’ QOL, a heightened awareness of, and early treatment for depression for frontline ED nurses should be provided.